COMPORTAMENTO DE VARIEDADES DE MANGUEIRA (Mangitera indica L.) EM RELAÇÃO A Aceria mangiferae (SAYED) (ACARINA: ERIOPHYIDAE) - Reis, Paulo Rebelles; Camargo, Ari Hoffmann de; Igue, Toshio; Rossetto, Carlos Jorge (REVISTA DE AGRICULTURA, 2016)
COMPORTAMENTO DE VARIEDADES DE MANGUEIRA (Mangitera indica L.) EM RELAÇÃO A Aceria mangiferae (SAYED) (ACARINA: ERIOPHYIDAE)